Break through the strength-ductility trade-off dilemma in aluminum matrix composites via precipitation-assisted interface tailoring. (1st January 2023) - Ma, Yu; Chen, Han; Zhang, Ming-Xing; Addad, Ahmed; Kong, Yi; Lezaack, Matthieu B; Gan, WeiMing; Chen, Zhe; Ji, Gang
Abstract: Strength-ductility trade-off is usually an inevitable scenario in most engineering materials, including metal matrix composites (MMCs) where reinforcement particles significantly degrade ductility. The decrease of ductility is mainly attributed to dislocation pile-ups at the high mismatch interface between reinforcement particles and matrix, which can not lead to effective dislocation multiplication and annihilation, finally leading to a low work hardening rate. To address this challenge, herein we propose a precipitation-assisted interface tailoring (PAIT) mechanism to improve the coherency of interface between reinforcement particles and matrix by introducing an interphase (IP). To achieve this PAIT mechanism, we design a manufacturing process combining the conventional casting, friction stir processing (FSP), hot extrusion with heat treatment. A TiB2 /Al-Zn-Mg-Cu composite fabricated with this process shows higher strength and ductility, which stand out from most available Al-based materials. In this composite, a Mg(Zn1.5 Cu0.5 ) IP is introduced to improve the coherency and strength of the TiB2 /Al interface by transforming the high mismatch TiB2 /Al interface into the low mismatch TiB2 /IP/Al multi-interfaces (i.e. sandwich structure). This effectively promotes dislocation multiplication and subsequent dislocation annihilation to increase the work hardening rate by restricting the dislocation pile-ups surrounding the interface, thus leading to a higher ductility. Our study aims to overcome the strength-ductility trade-off of MMCs by tailoring interface structure, which can provide insight into the production of high-performance MMCs. Graphical abstract: Image, graphical abstract